Neutrophil extracellular traps as the main source of eDNA - Cieśluk, Mateusz; Piktel, Ewelina; Wątek, Marzena; Durnaś, Bonita; Wollny, Tomasz; Król, Grzegorz; Bucki, Robert (Medical Studies/Studia Medyczne, 2017)
Neutrophil extracellular traps (NETs) are web-like structures consisting of decondensed DNA together with accompanying proteins, including histones and antimicrobial peptides released from activated neutrophils as part of the first-line defence against pathogens. Despite the protective role of neutrophils, a number of studies indicate that overproduction of NETs followed by accumulation of extracellular DNA (eDNA) and other negatively-charged polyelectrolytes (PE) such as F-actin, contribute to the pathogenesis of some diseases. Neutrophil extracellular traps are also recognised as the structural and functional support of microbial biofilms and should thus be considered as therapeutic targets. Importantly, the chemical nature of PE permits aggregate formation induced by a number of polycations occurring naturally in the human body, including cationic antimicrobial peptides. This review summarises recent reports focused on the clinical significance of NET-derived eDNA and PE and discusses the potential therapeutic strategies to limit the negative consequences of eDNA accumulation.